2023
DOI: 10.1021/acsami.3c09635
|View full text |Cite
|
Sign up to set email alerts
|

Rhodium-Doped Barium Titanate Perovskite as a Stable p-Type Photocathode in Solar Water Splitting

Ke Shi,
Boyang Zhang,
Kaiwei Liu
et al.

Abstract: Solar water splitting from a p−n-conjugated photoelectrochemical (PEC) system is a promising way to produce hydrogen sustainably. At present, finding a compatible p-type photocathode material for the p−n system remains a great challenge in consideration of the photocurrent and stability. This paper highlighted a promising candidate, Rh/BaTiO 3 , by switching BaTiO 3 from an n-type photoanode to a p-type photocathode upon Rh doping. The dopant activated visible light absorption up to 550 nm and an onset potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
15
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 54 publications
3
15
0
Order By: Relevance
“…almost a decade ago . Recently, Shi et al investigated the effect of the Rh doping level on the Fermi level position and n- to p-type transition was studied by isolating the cathodic contribution by the Rh dopant . Despite years of research related to BTO as a H 2 evolution photocatalyst, there exists no report investigating the effect of the dopant’s valence state on the optoelectronic properties and subsequent photocatalytic and/or photoelectrochemical behavior of BTO.…”
Section: Introductionmentioning
confidence: 99%
“…almost a decade ago . Recently, Shi et al investigated the effect of the Rh doping level on the Fermi level position and n- to p-type transition was studied by isolating the cathodic contribution by the Rh dopant . Despite years of research related to BTO as a H 2 evolution photocatalyst, there exists no report investigating the effect of the dopant’s valence state on the optoelectronic properties and subsequent photocatalytic and/or photoelectrochemical behavior of BTO.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the transformation of an SrTiO 3 perovskite oxide from an n-type to a p-type semiconductor could be achieved by introducing acceptor energy levels above its valence band, thereby effectively lowering the Fermi level. The result was a high onset potential up to 1.0 V versus the RHE as well as extended light absorption from the ultraviolet (UV)-responsive oxide host to the visible region. Similarly, our group has introduced a Rh dopant into BaTiO 3 , which created deep acceptor levels above the valence band and thus realized photocurrent switching from anodic to cathodic . An onset potential of 1.1 V versus the RHE was obtained on the Rh:BaTiO 3 photocathode, and its edge of light absorption was extended from 380 to 550 nm.…”
mentioning
confidence: 95%
“…In this work, we employ the Rh-doped rutile TiO 2 electrode as an example to illustrate the great potential of gradient doping for enhancing photocurrent and transformation from photoanode to photocathode. Unlike many other reports that induce a full transformation of TiO 2 from n-type to p-type by heavy doping, ,,, a minimum amount of Rh dopant is used in this work to keep its n-type nature. First, the Rh dopants with a graded distribution create upward band bending along the direction of higher doping concentration near the rutile particle surface.…”
mentioning
confidence: 99%
“…However, the poor stability of these materials, even with protection layers, remains a major challenge. Ti­(IV)-based oxides, such as TiO 2 , SrTiO 3 , and BaTiO 3 possess remarkable stability over a wide range of operating conditions, and more importantly, they can act as p-type photocathodes upon doping with certain transition metal elements. Rhodium is an effective dopant that can extend the light absorption of the UV­(ultraviolet)-responsive Ti­(IV)-based oxides to visible region by introducing intragap states. Such intragap states also act as acceptor energy levels above the valence band of the titanate host (O 2p), and a heavier concentration of the Rh dopant leads to a lower Fermi level of the semiconductor. With a Rh doping level higher than 2 mol %, the Ti­(IV)-based oxides have frequently been switched from n-type to p-type, i.e.…”
mentioning
confidence: 99%
See 1 more Smart Citation